Opportunities and Challenges to Improve Postpartum Care: Payors’ and Purchasers’ Perspectives in California - Lindsay Parham; Renee Clarke; MariaDelSol De Ornelas; Sabrina Li; Sylvia Guendelman (Women's Health Reports)
Introduction: U.S. maternal mortality rates are two to three times higher than other high-income countries, with most deaths occurring postpartum. Fragmented care, exacerbated by health insurance gaps and workforce shortages, underscores systemic deficiencies. Although patients’ and clinicians’ perspectives are well-documented, little is known about payors’ and purchasers’ perspectives. Given their influence in coverage decisions, payment rates, and service reimbursement, the objective was to explore their perspectives and identify challenges and opportunities in improving postpartum care in California, currently engaged in reshaping maternal health pathways. Methods: We conducted a qualitative study using semi-structured interviews with high-level administrators from major California health insurance providers and purchasers between June and October 2023. Participants, recruited through professional connections, were selected through purposive sampling based on their involvement in maternal and child health coverage decisions. A hybrid inductive–deductive approach was employed to identify major themes. Results: Participants (n = 11) identified barriers including limited insurance coverage, lack of clinical provider incentives, reimbursement concerns, and misaligned measures and metrics. Opportunities to improve postpartum care focused on visit timing and frequency, alternative payment models, and improving continuity of care between birth and the transition to primary care. Conclusions: Insurance payors and purchasers identified postpartum care barriers and suggested solutions well-supported by the literature. These solutions—including reimagining global bundle payment models, updating Healthcare Effectiveness Data and Information Set measures, and promoting dyadic models—could address barriers, improve outcomes, and inform California’s ongoing maternal health transformation and those happening around the United States.